Elective cholecystectomy as a rare presentation of metastatic breast cancer. Issue 11 (13th November 2018) - Magalhães, Joana S; Matos, Leonor; Santos, Teresa; Nora, Mário
Abstract: Cholecystectomy leads, occasionally, to the diagnosis of subclinical primary carcinomas and rarely metastatic tumors. The authors report the diagnosis of gallbladder metastasis after an elective cholecystectomy for symptomatic cholelithiasis. Histological examination disclosed a metastasis from a lobular breast carcinoma. Authors found no more than 25 case reports of breast cancer metastasis in English literature. Of those, only one reports first diagnosis after elective cholecystectomy with no radiological or macroscopic signs of malignancy. Rare clinical presentations, as in this case, should always be kept in mind specially in high volume centers. These rare presentations lack good quality evidence and challenge the best standard treatment regimen available. Multidisciplinary assessment is the key to maximize the risk/benefit of different treatment modalities. In this case report, although curative surgery was attempted, progression disease was typical of an advance staged disease.